Formation and characterization of solvent resistant nanofiltration membranes - Wijaya, Julie E (University of Ottawa (Canada), 2005)
In this work, a novel approach for preparing nanofiltration membranes using poly(amide imide) (TorlonRTM)/Chitosan composites by coating the Chitosan solution on top of the Torlon base membrane and subsequently curing and neutralization with sodium bicarbonate (NaHCO3) has been developed. In general, TorlonRTM/Chitosan composite nanofiltration membranes were found to be stable in aqueous medium and when contacted with the solvents. A uniform Chitosan dense layer was successfully coated on the base membrane, which reduced the effect of chemical degradation of the membrane. Low permeability of solvents was attributed to the swelling of the Torlon RTM layer. It is proposed that by increasing the porosity in the TorlonRTM based membrane or utilizing other polymers which contain amide chains as the support membrane, permeability performance could be enhanced. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.